Synthesis of agro-industrial wastes/sodium alginate/bovine gelatin-based polysaccharide hydrogel beads: Characterization and application as controlled-release microencapsulated fertilizers - Yetilmezsoy, Kaan; Kiyan, Emel; Ilhan, Fatih (ELSEVIER, 2024)
Synthesis of novel agro-industrial wastes/sodium alginate/bovine gelatin-based polysaccharide hydrogel beads, micromeritic/morphometric characteristics of the prepared formulations, greenhouse trials using controlled-release microencapsulated fertilizers, and acute fish toxicity testing were conducted simultaneously for the first time within the scope of an integrated research. In the present analysis, for the first time, 16 different morphometric features, and 32 disinct plant growth traits of the prepared composite beads were explored in detail within the framework of a comprehensive digital image analysis. The hydrogel beads composed of 19 different agro-industrial wastes/materials were successfully synthesized using the ionotropic external gelation technique and CaCl2 as cross-linker. According to micromeritic characteristics, the ionotropically cross-linked beads exhibited 77.86 +/- 3.55 % yield percentage and 2.679 +/- 0.397 mm average particle size. The dried microbeads showed a good swelling ratio (270.02 +/- 80.53 %) and had acceptable flow properties according to Hausner's ratio (1.136 +/- 0.028), Carr's index (11.94 +/- 2.17 %), and angle of repose (25.03 degrees +/- 5.33 degrees) values. The settling process of the prepared microbeads was observed in the intermediate flow regime, as indicated by the average particle Reynolds numbers (169.17 +/- 82.81). Experimental findings and non-parametric statistical tests reveal that dried fertilizer matrices demonstrated noteworthy performance on the cultivation of red hot chili pepper plant (Capsicum annuum var. fasciculatum) according to the results of greenhouse trials. Surface morphologies of the best-performing fertilizer matrices were also characterized by Scanning Electron Microscopy. Moreover, the static fish bioassay experiment confirmed that no abnormalities and acute toxic reactions occurred in shortfin molly fish (Poecilia sphenops) fed with dried leaves of red hot chili pepper plants grown with formulated fertilizers. This study showcased a pioneering investigation into the synthesis of microcapsules using synthesized hydrogel beads along with digital image processing for bio-waste management and sustainable agro-application.
Keywords: Acute toxicity; Controlled-release fertilizer; Cross-linking; Digital image analysis; Greenhouse study; Ionotropic external gelation; Microencapsulation; Sodium alginate; MANURE WASTE-WATER; CALCIUM-ALGINATE; DRUG-DELIVERY; GROWTH; SEEDLINGS; VELOCITY; CHITOSAN; MATRIX; SLUDGE; COD; Biochemistry & Molecular Biology; Chemistry; Polymer Science